Illustrating the discussions on Ottoman studies in the early Republican Turkey through Tayyib Gökbilgin - Altın, Kutse (Études sur la Région Méditerranéenne, 2020)
Tayyib Gökbilgin, who ranks among the founding fathers of Ottoman studies was one of the most influential historians of the early period of the Turkish Republic. He was also one of the prominent historians who conducted numerous researches on Ottoman–Hungarian historical relations. Gökbilgin was the first student of Faculty of Language, History, and Geography (Dil, Tarih, Coğrafya, Fakültesi) in the new capital of the new state, namely in Ankara where he began studying Hungarology/Hungarian Studies as a student of László Rásonyi. The modern practice of history and the advancement of the nation-state progressed side by side and Tayyib Gökbilgin had maintained his modernist Turkish nationalist identity and emphasized that one of the fundamental aims of history was to feel proud with the historical past of the Turks. One can coincide with this statement in almost all historians of the period since it was the clearest example of efforts to legitimize Ottoman history as a part of World history. Tayyib Gökbilgin, like the way his contemporaries, followed the mission of his professor Fuad Köprülü and tried to reveal the truth of the matters that the western world conceptualized incorrectly with incomplete materials, with the capability provided by the authority given by the utilization of the original sources. He, like many of his colleagues, had also a particular interest, an intellectual purpose of breaking down the prejudices against the Ottomans and thus the Turks. It would not be wrong to state that his historiography emerged from this core. However, it also does not mean that he creates an Ottoman admiration or exaltation adorned with unnecessary heroic stories at the opposite end while trying to realize his purpose. What I plan to proceed in this presentation is to evaluate Tayyib Gökbilgin’s contribution to writing Ottoman History and efforts to legitimize Ottoman History as a part of World History while maintaining his modernist Turkish nationalist identity that was formed by the developments within nation-building process in the late Ottoman and early Republican era.